Cost Effectiveness of Different Containerized Nursery Technologies - Gera, Mohit; Singh, A. K.; Chand, Pritam (Indian Forester, 2003)
Modern nursery methods of seedling production , viz. , 150cc and 300cc root trainers , improved polythene bag seedling production system (Mounted Angle Iron beds) were compared with the conventional nursery production system by raising of seedlings of four tree species viz. , Acacia catechu , Albizia lebbek , Azadirachta indica and Pinus roxburghii , on the basis of costs involved and benefits rcceived. In order to bring commonality of comparisons , the study involved raising of 8000 seedlings every year using selected seedling production systems on continuous basis for ten years. The results have revealed that seedlings raised on Mounted Angle Iron (MAI) beds recorded not only appreciable values on height and collar diameter but also gave better values on seedling quality parameters. Also , the seedlings raised on MAI beds were found to be most cost effective when compared with other nursery systems on the basis of benefit cost analysis.